Multidrug-resistant bacteria in a paediatric palliative care inpatient unit: results of a one year surveillance - Schmidt, Pia; Hasan, Carola; Simon, Arne; Geffers, Christine; Wager, Julia; Zernikow, Boris (German Medical Science GMS Publishing House, 2020)
Aim: Nosocomial infections (NIs) and multidrug resistant (MDR) pathogens are an important paediatric healthcare issue. In vulnerable patients such as children with life-limiting conditions, MDR infections can be life-threatening. Additionally, these children have a significantly increased risk for colonisation with MDR pathogens. Therefore, it is vital to prevent new colonisations with MDR pathogens in this vulnerable patient group. However, little is known about colonisation with MDR pathogens and NIs in inpatient units for paediatric palliative care (PPC). The aim of this study was to investigate the prevalence of colonisation with MDR pathogens and the incidence of NIs in a PPC unit.Methods: Evaluation of surveillance data of a PPC unit. All patients admitted to a PPC unit from 1 April 2012 to 31 March 2013 were screened for MDR pathogens upon admission. Patients who exhibited clinical signs of an infection during their inpatient stay were screened again. Results: During the study period, 198 cases were admitted to the unit. Those cases represent 118 patients. 18% of the patients were colonised with MDR pathogens. The most common MDR pathogens were (8.1%) and (8.1%). In addition, 58% of patients with tracheostomy had MDR pathogens in their tracheal secretions. The incidence density of NIs was 0.99 per 1000 inpatient treatment days with no NI caused by MDR pathogens.Conclusion: Due to a high prevalence, it is reasonable to screen PPC patients for MDR pathogen colonisation before or during admission. Special attention must be given to patients with tracheostomy. Our results provide preliminary evidence that participation in social activities in a PPC unit for patients colonised with MDR pathogens is safe if hygiene concepts are applied.